A 2-bit Adaptive Delta Modulation System with Improved Performance. (16th November 2006) - Prosalentis Prosalentis, E. A. E. A.; Tombras Tombras, G. S. G. S.
Abstract : A 2-bit adaptive delta modulation system with improved performance is proposed in this paper. Its main characteristic is a new adaptation algorithm that incorporates both memory and look-ahead instantaneous step-size estimation and leads the modulator into generating a 2-bit output codeword. As shown by computer simulation results, the proposed system offers reduced overshoot and fast response to signal variations in comparison to other similar systems.